2020
DOI: 10.1002/admt.202000430
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Silk Fibroin Ionotronic Skin for Temperature Sensing

Abstract: The emergence of ionotronic materials has substantially extended the applications of artificial skins by allowing intimate interfaces between electronics and biological/bionic surfaces toward achieving improved sensing and communication with surrounding stimuli. However, ionotronic skins are intrinsically temperature dependent, since water molecules play crucial roles in regulating both mechanical and ionic conductivity of the materials. Hence, most of the ionotronic skins will fail at temperatures below 0 °C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…Elevated temperature at wound sites is a well‐established marker of infection and can be employed as an early indicator of chronic wounds. [ 77 ] Test in an ex vivo wound model demonstrated that the resistance of MiS was responsive to temperature with a relatively high sensitivity and responsiveness, [ 78,79 ] with the change in resistance strongly correlated to the change in temperature (Figure 6e and Figure S7: Supporting Information). This indicated that the MiS was capable of timely monitoring the wound temperature to allow identification of emerging inflammation or infection.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated temperature at wound sites is a well‐established marker of infection and can be employed as an early indicator of chronic wounds. [ 77 ] Test in an ex vivo wound model demonstrated that the resistance of MiS was responsive to temperature with a relatively high sensitivity and responsiveness, [ 78,79 ] with the change in resistance strongly correlated to the change in temperature (Figure 6e and Figure S7: Supporting Information). This indicated that the MiS was capable of timely monitoring the wound temperature to allow identification of emerging inflammation or infection.…”
Section: Resultsmentioning
confidence: 99%
“…SF/CaCl 2 membranes (weight ratio of 3/1) were used as the starting material for HHSMs preparation, it can stretch by more than 7‐fold in length and is present in a highly hydrated state (water content of 54 ± 3%), since CaCl 2 has good hygroscopicity and a calcium ion could capture six water molecules from the surroundings through coordination interactions, thus plasticizing silk proteins membranes ( Figure a ). [ 21–24 ]…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the silk in this Silk/CaCl 2 membrane was amorphous and primarily stabilized by intermolecular hydrogen bonds and ion chelation. [ 21–24 ] Thus, the resultant materials appeared with a gum‐like soft state, where small forces induced large deformations. Therefore, β‐sheet crosslinks among the chains were required, akin to natural silk (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 93 ] Additionally, silk fibroin films have also been used to fabrication of flexible and wearable electronic skins for monitoring human physiological responses. [ 94,95 ] Recently, wearable electronic devices have been developed using protein nanowire films for humidity sensing. [ 96 ] Composite materials of amyloid aggregates and graphene have exhibited shape memory and enzyme sensing properties.…”
Section: Applications Of Protein Coatingsmentioning
confidence: 99%